2020
DOI: 10.1002/adom.202001016
|View full text |Cite
|
Sign up to set email alerts
|

Polaron and Spin Dynamics in Organic–Inorganic Lead Halide Perovskite Nanocrystals

Abstract: Long‐lived carrier population and spin‐based behavior in lead halide perovskite nanocrystals (NCs) are extremely interesting for implementing photovoltaic devices with efficiencies exceeding the Shockley–Queisser limit and quantum information processing, respectively. However, a comprehensive understanding of polaron‐mediated charge carrier interactions and an accurate description of the spin‐polarized states for spintronics are still lacking. Herein, the carrier and spin interactions are studied under control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…30−33 Their low-cost solution processability and ease of integration with an existing nanofabrication facility make them much more attractive. 34,35 Moreover, their strong band-edge exciton− photon coupling, 36 defect-tolerant electronic structure of a trap-free nature, 34,35,37−39 discrete and narrow-bandwidth exciton transitions, 5,11,39 and scalable production of highly coherent quantum emitters 37,40 make them an ideal candidate for the study of coherent and spin-selective light−matter interactions at room temperature. In addition, the multiexciton interactions in MHP QDs, in particular, CsPbBr 3 , are reasonably strong 32,41 and thus can influence the coherent light−matter interactions.…”
mentioning
confidence: 99%
“…30−33 Their low-cost solution processability and ease of integration with an existing nanofabrication facility make them much more attractive. 34,35 Moreover, their strong band-edge exciton− photon coupling, 36 defect-tolerant electronic structure of a trap-free nature, 34,35,37−39 discrete and narrow-bandwidth exciton transitions, 5,11,39 and scalable production of highly coherent quantum emitters 37,40 make them an ideal candidate for the study of coherent and spin-selective light−matter interactions at room temperature. In addition, the multiexciton interactions in MHP QDs, in particular, CsPbBr 3 , are reasonably strong 32,41 and thus can influence the coherent light−matter interactions.…”
mentioning
confidence: 99%
“…A number of spectroscopic and optical measurements, such as time-resolved optical Kerr effect spectroscopy, time-resolved two-photon photoemission, transient reflectance, and absorption spectroscopies, time-domain Raman spectroscopy, angle-resolved photoelectron spectroscopy, have been used to reveal the electron-phonon (e-ph) coupling in CsPbBr 3 [32][33][34] , MAPbBr 3 [35][36][37] , and MAPbI 3 [38][39][40][41][42] . However, these measurements are associated with the large polaron formation either from the phonon or from the electronic structure perspective [42][43][44] (See Supplementary Table S1 for a literature survey). In addition, it is challenging, to use an ultrafast spectroscopic technique in the visible region to access the polaron mobility, carrier scattering parameters, and dynamics in MHPs quantitatively, which are considered as the fundamental nature of the large polaron 29,45 .…”
Section: Introductionmentioning
confidence: 99%
“…For free carriers, several studies have suggested that the carriers be transferred to spatially localized states arising from interacting electrons and phonons, known as polarons. Such a polaron formation can protect the free carriers (electrons and holes) from recombination, eventually elongating the carrier lifetime. Recent experiments have shown a correlation between the rotation dynamics of organic cations and carrier lifetime for 3D perovskites, suggesting that the rotation dynamics of cations can promote the formation and stabilization of polarons. ,, Specifically, the monocationic charge on MA is localized on the −NH 3 + group and forms a cationic rotor in the PbI 3 – cage. In this case, the free carriers attract/repel multiple cations in their proximity presumably via electrostatic interaction and wavefunction overlapping, leading to a polaron consisting of a carrier–multi-ion entity (Figure b).…”
Section: Resultsmentioning
confidence: 99%